A WEB BASED 8-PUZZLE EDUCATIONAL GAME FOR RECOGNIZING SULAWESI’S ENDEMIC ANIMALS USING THE BFS ALGORITHM - Muchtar, Mutmainnah; Wellem, Karmila Alamsyah (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
The advancement of AI (artificial intelligence) has provided new opportunities to enhance learning through interactive digital media. This study presents the development of a web based 8-Puzzle educational game designed to introduce Sulawesi’s endemic animals using the BFS (Breadth First Search) algorithm. The system was developed using HTML, CSS, and JavaScript, and tested in a web browser environment on Windows 11. The waterfall method was applied during system development. Black-box testing ensured that all functions, such as shuffle, reset, navigation, and information display, operated correctly. Performance evaluation was carried out on 12 puzzle configurations, measuring solution steps, nodes expanded, and execution time. The results show that the BFS algorithm effectively solved all puzzles with optimal accuracy, producing solution times ranging from 1 ms to 140 ms depending on puzzle complexity. This research demonstrates how AI algorithms can be integrated into educational games to promote both problem solving skills and environmental awareness.